Metaphor and ideology : liber antiquitatum biblicarum and literary methods through a cognitive lens - DesCamp, Mary Therese (Biblical interpretation series ;, 2007)
Contemporary scholars have sharply disagreed over the importance of the loquacious women of ""Liber Antiquitatum Biblicarum, "" Using the methods of contemporary Cognitive Linguistics, ""Ideology and Metaphor"" develops a systematic, replicable reading of the text and its characters, showing how Pseudo-Philo uses these women's stories to articulate the text's theology and ideology. The analysis also explores how the author redefines the term mother in order to sanction the female authority to interpret and instruct. The conceptual blends that compose the text's distinctive and sometimes dissona